Isolated and Combined Effect of Resistance Training and Plyometric Training on Explosive Power Performance Variables among Women Volleyball Players: The effect of resistance and plyometric training on vertical jump performance among women volleyball players (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study was undertaken to analyze the effect of isolated and combined effect of resistance training and plyometric training on explosive performance among women volleyball players. The investigator has selected N=80 women inter collegiate levelstate level participated volleyball players at random from various college of the YSR Kadapa district of Andhra Pradesh, India and their age range from eighteen to twenty five years as per their college record. The volleyball players chosen for the study were divided into four equal groups n=20 and designated as experimental group ‘A’ experimental group ‘B’ experimental group ‘C’ and control group ‘D’. polyometric exercises training were given to group ‘A’ resistance exercises training were given to group ‘B’, Combined training of plyometric exercises and resistance exercises training were given to group ‘C’ and the ‘CG’ control group ‘D’ were restricted to participate in any activities. The trainings were given for a period of twelve weeks. The data were collected before and after the training by conducting vertical jump. The obtained data’s were analyzed by Analysis of Covariance (ANCOVA). The level of significant was fixed at 0.05 levels. The results of the study showed that plyometric exercises, resistance exercises and combined training significantly improved vertical jump performance of the volleyball players when comparative with control group. The Combined training group volleyball players shown better performance in vertical jump performance test when comparison with plyometric exercise training group and resistance exercises training group volleyball players.